2020
DOI: 10.3389/fphys.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in Aortic Dissection

Abstract: Aortic dissection (AD) is a fatal disease that accounts for a large proportion of aorticrelated deaths and has an incidence of about 3-4 per 100,000 individuals every year. Recent studies have found that inflammation plays an important role in the development of AD, and that macrophages are the hub of inflammation in the aortic wall. Aortic samples from AD patients reveal a large amount of macrophage infiltration. The sites of macrophage infiltration and activity vary throughout the different stages of AD, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 72 publications
(94 reference statements)
0
51
0
1
Order By: Relevance
“…Macrophages, which have both anti-inflammatory and inflammatory effects, are related to the pathophysiology mechanism of AD. 27 Macrophages play multiple roles in TAAD and the release of VEGF by macrophages is positive in the tunica media, and all AAD samples show immune-inflammatory infiltration and vessel growth. 28 As the dominant inflammatory cells in acute inflammation, neutrophils mainly infiltrate the adventitia of AD tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Macrophages, which have both anti-inflammatory and inflammatory effects, are related to the pathophysiology mechanism of AD. 27 Macrophages play multiple roles in TAAD and the release of VEGF by macrophages is positive in the tunica media, and all AAD samples show immune-inflammatory infiltration and vessel growth. 28 As the dominant inflammatory cells in acute inflammation, neutrophils mainly infiltrate the adventitia of AD tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that in ammation, angiogenesis, activation of transforming growth factor-β1 (TGF-β1) signaling pathway and degradation of extracellular matrix, abnormal phenotypic transition of vascular smooth muscle cells (VSMCs) is mainly involved in the pathogenesis of AAD. However, the detailed molecular mechanism remains to be explored [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…And it can subsequently develop to systemic inflammatory reactions syndrome (SIRS) due to uncontrolled inflammatory cascade [17]. Aortic samples from the patients with aortic dissection revealed a large amount of macrophages infiltration [18]. A large number of cytokines have also been found infiltrating the aortic wall of patients with aortic dissection, such as IL-6 and IL-17 [12].…”
Section: Discussionmentioning
confidence: 99%